From Elmolo to Gura Pau: A remembered Cushitic language of Lake Turkana and its possible revitalization - Mauro Tosco (LibraryPress@UF, 2015)
This article discusses the “extinct” Elmolo language of the Lake Turkana area in Kenya. A surprisingly large amount of the vocabulary of this Cushitic language (whose community shifted to Nilotic Samburu in the 20th century), far from being lost and forgotten, is still known and is, to a certain extent, still used. The Cushitic material contains both specialized vocabulary (for the most part related to fishing) and miscellaneous and general words, mostly basic lexicon. It is this part of the lexicon that is the basis of recent revitalization efforts currently undertaken by the community in response to the changing political situation in the area. The article describes the Cushitic material still found among the Elmolo and discusses the current revitalization efforts (in which the author has, albeit marginally, taken part), pinpointing its difficulties and uncertain results. The article is followed by a glossary listing all the Cushitic words still in use or remembered by at least a part of the community.